DETERMINANTS OF THE USE OF AGRO-INPUTS IN THE REDUCTION OF GREENHOUSE GAS EMISSION IN COMMERCIAL CHICKEN FARMS IN SELECTED STATES OF NIGERIA - Oyoboh, D.E.; Irhivben, B.O.; Oyita, G.E.; Inoni, O.E.; Omotesho, O.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the determinants of the use of agro-inputs in the reduction of greenhouse gas emission in commercial chicken farms in selected States of Nigeria. A structured questionnaire was used to collect the quantitative data used for the study through a two-stage sampling technique. The first stage involved a purposive selection of the selected states which are commercial chicken production hubs in Nigeria. The second stage was proportion-to-size random sampling selection of 349 commercial farms using the register of the Poultry Association of Nigeria (PAN) the umbrella body of poultry farmers in Nigeria as sampling frame. The study made used of primary data collected in the previous production season with the aid of semi-structured questionnaire. The managers of the selected farms were interviewed and the data collected using the questionnaire and a checklist of commercial chicken farms groups. Data were obtained on socio-economic characteristics and access to agro-inputs that could reduce greenhouse gas emission. The analytical methods used in the study included descriptive statistics and binary logistic regression to model the factors influencing socio-economic and access to these agro-inputs. Findings revealed that most chicken farms in Nigeria have limited access to key inputs like high quality feed (59.6%) and circulation fans (58.6%), affecting their ability to manage emissions effectively. Significant determinants of access to inputs included capital investment (odd ratio =3.86), farm age (odd ratio=1.11) and revenue (odd ratio=2.83). The study concludes that Nigerian chicken farms are currently ill-equipped to handle greenhouse gas emissions adequately, high lighting a need for improved management practices to mitigate the pains it has on the risk to health of the human and the environment.